Effect of Quenching Media on Corrosion Resistance of Al-Si-Mg Alloy - Mousa Al-Uqaily, et.al, Dr.Abdulazeez O. (Al-Qadisiyah Journal of Pure Science, 2017)
This study aims to preparing of Al-Si-Mg alloy and study the effect of quenching media (polymer solution and water) on the properties of prepared alloy such as corrosion resistance in 3.5% NaCl , surface roughness and microstructure. Also study the effect of addition alloying elements (Boron and Titanium) on above properties of prepared alloy. The results showed that improvement in corrosion resistance and surface softness of prepared alloys when addition of boron and titanium to the prepared alloy and when quenched in polymer solution. Optical microscopic results showed that the microstructure of prepared alloys when quenched in polymer solution consists of shape, size and uniform distributing for grains in comparison with the same alloys when quenched in water.